Poly(D,L-Lactic Acid) Nanoparticle Size Reduction Increases Its Immunotoxicity - Da Silva, Jessica; Jesus, Sandra; Bernardi, Natália; Colaço, Mariana; Borges, Olga (Frontiers in Bioengineering and Biotechnology, 2019)
Polylactic acid (PLA), a biodegradable and biocompatible polymer produced from renewable resources, has been widely used as a nanoparticulate platform for antigen and drug delivery. Despite generally regarded as safe, its immunotoxicological profile, when used as a polymeric nanoparticle (NP), is not well documented. Thus, this study intends to address this gap, by evaluating the immunotoxicity of two different sized PLA NPs (PLAA NPs and PLAB NPs), produced with different nanoprecipitation methods and extensively characterized regarding their physicochemical properties in in vitro experimental conditions. After production, PLAA NPs mean diameter was superior to PLAB NPs. Interestingly, when in RPMI medium, both presented similar mean size and zeta potential, possibly explaining the similarity between their cytotoxicity profile in PBMCs. On the other hand, in DMEM medium, PLAA NPs presented smaller mean diameter, which may explain its higher toxicity in RAW 264.7. Likewise, PLAA NPs induced a higher dose-dependent ROS production, which can explain their toxicity in this cell line. Irrespective of size differences, none of the PLA NPs presented an inflammatory potential characterized by NO production or a hemolytic activity in human blood. The results herein presented suggest that smaller PLA NPs (<100 nm) possess increased toxicity. Furthermore, this study emphasizes the importance of interpreting results based on adequate physicochemical characterization of nanoformulations in biological media. As observed, small differences in size triggered by the dispersion in cell culture media can have repercussions on immunotoxicity, and if not correctly evaluated can lead to misinterpretations, and subsequent ambiguous conclusions.